Collaboration on International Community Service to Promote Clean and Healthful Living Practices in Malaysia - Imran Pashar; Indira Fitriliani; Zain Ahmad Fauzi; Encik Shahrin Hasyim; Syifa Anida Zahra; Tria Monika Tambun; Qaila Qaila; Tiara Nurhaliza (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
In order to improve children's health and prevent communicable diseases, Clean and Healthy Living Behavior should be taught starting in elementary school. Washing your hands properly with soap is one of the simplest Clean and Healthy Living Behavior routines to follow Through instructional exercises and hands-on demonstrations, this community service program sought to improve students' understanding of Clean and Healthy Living Behavior and Washing your hands properly with soap. Thirty primary school kids participated in the program, which was held on May 6, 2026, at SK Felda Kledang in Johor, Malaysia. Interactive lectures, demonstrations, and practical use of the six-step handwashing process were among the techniques used. The findings showed that every activity went off without a hitch and that participants were quite enthusiastic about the entire program. Pupils were able to comprehend the fundamental ideas of PHBS, appreciate the value of environmental and personal hygiene, and successfully complete the six-step handwashing process on their own. The use of direct demonstration techniques were successful in assisting participants in understanding the topic, despite difficulties arising from vocabulary differences between the Indonesian and Malaysian languages. Overall, the program was successful in raising students' understanding of the significance of incorporating clean and healthy living practices into their everyday lives.